Gelation mechanism of high soluble dietary fiber okara-egg tofu induced by combined treatment of steam explosion and enzymatic hydrolysis. (July 2023) - Zhao, Nuo; Wu, Jianfu; Geng, Xiaoyuan; Wang, Chenyang; Wu, Tao; Liu, Rui; Sui, Wenjie; Zhang, Min
Abstract: Okara contains a large amount of insoluble dietary fiber (IDF), but it is usually treated as waste. This study was to develop a high soluble dietary fiber (SDF) egg tofu. The SDF content in okara was increased by steam explosion and enzymatic hydrolysis. The gelation mechanism of high SDF egg tofu was evaluated by adding modified okara (MO), non-modified okara (NMO) and available fraction of modified okara (AMO) into the egg tofu. The results showed that the content of SDF in okara was increased from 2.14% to 32.13% after modification. The content of SDF in high SDF egg tofu (MO Gel) was about 2.6 times that of ordinary egg tofu (Control Gel). The texture and rheological properties showed that the addition of MO and NMO improved hardness and viscoelasticity of egg tofu, while the addition of AMO destroyed the gel network structure. The addition of MO and NMO enhanced the WHC of egg tofu, while the addition of AMO promoted the immobilized water to free water, and the microstructure characterization laterally confirmed it. The above results proved that the insoluble dietary fiber (IDF) in MO and NMO played a positive role in egg tofu gel. Only addition of SDF (AMO Gel) destroyed the network structure of egg tofu gel, while the presence of appropriate content of IDF was conducive to enhance the stability of gel structure. This work provided theoretical understanding for the preparation of high SDF egg tofu. Graphical abstract: Image 1 Highlights: The combined modification by steam explosion and enzymatic hydrolysis increased the SDF content from 2.14% to 32.13%. Compared with ordinary egg tofu, the SDF content of high-SDF egg tofu was increased by 10.07%. The presence of IDF enhanced the hardness, viscoelasticity, water holding capacity, and disulfide bond of egg tofu gel. The formation of egg tofu gel with high SDF content required a certain amount of IDF to enhance gel stability.